Identifikasi Karakteristik, Kebutuhan, dan Minat Pengrajin Tempe (Studi Kasus di Kampung Tempe Kota Pekalongan) - Yuliando, Henry; Purwadi, Didik; Naziha, Thalia; Putri Pradita, Sintia; Ida Gunawati, Amalia; Kartika Dewi, Mutiara (Badan Perencana Pembangunan, Riset dan Inovasi Kota Pekalongan, 2024)
Pekalongan City, which has more than 100 tempeh producers, is in Kuripan Kertoharjo Village, making this village known as